2014
DOI: 10.1097/apo.0b013e3182a141e7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Wound Morphology of Sclerotomy Sites of Sutureless Vitrectomy Using Spectralis Anterior Segment Optical Coherence Tomography

Abstract: In both groups, the sclerotomy incisions showed good healing at 1-month duration. The 25-gauge sclerotomies showed better healing characteristics of wound morphology as compared with the 23-gauge sclerotomies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…OCT images of the 23-gauge MVR blade incisions also showed earlier wound closure compared with beveled trocars 26. In a recent study of wound morphology in human eyes undergoing vitrectomy with incisions created using a 23- or 25-gauge ridged MVR blade, both gauge MVR blades led to complete wound closure and no leakage;29 our results are in general agreement with these findings. Together, these studies suggest that the morphologic differences among incisions created with trocar blades of different designs may influence wound closure.…”
Section: Discussionsupporting
confidence: 90%
“…OCT images of the 23-gauge MVR blade incisions also showed earlier wound closure compared with beveled trocars 26. In a recent study of wound morphology in human eyes undergoing vitrectomy with incisions created using a 23- or 25-gauge ridged MVR blade, both gauge MVR blades led to complete wound closure and no leakage;29 our results are in general agreement with these findings. Together, these studies suggest that the morphologic differences among incisions created with trocar blades of different designs may influence wound closure.…”
Section: Discussionsupporting
confidence: 90%
“…[ 2 ] Wound healing in 25G sclerotomies, as graded by the AS-OCT, is seen to be complete by 2 weeks to 1 month after surgery. [ 25 ] Among the gradable sclerotomies in our study, irrespective of the quadrant analyzed, the odds of having an open sclerotomy tract was found to be more than 5 in patients who had circumferential sclerotomies and a statistically significant difference was found in SNQ. Research has shown that centrifugal forces directed outward from within the eye are important for the closure of a beveled incision on the eye wall.…”
Section: Discussionmentioning
confidence: 64%
“…Since then, the instrumentation has evolved from the original 17-gauge cutter to micro-incision vitrectomy surgery (MIVS) [6, 7]. Smaller sutureless sclerotomy wounds result in less postoperative inflammation, greater postoperative patient comfort, and possibly faster postoperative visual recovery [8, 9]. On the other hand, innovations to the viewing system have included the contact lens and noncontact lens wide angle viewing systems (WAVS).…”
Section: Introductionmentioning
confidence: 99%